2018
DOI: 10.3389/fmicb.2018.01276
|View full text |Cite
|
Sign up to set email alerts
|

Oenococcus oeni Exopolysaccharide Biosynthesis, a Tool to Improve Malolactic Starter Performance

Abstract: Oenococcus oeni is the lactic acid bacterium that most commonly drives malolactic fermentation (MLF) in wine. Though the importance of MLF in terms of wine microbial stability and sensory improvement is well established, it remains a winemaking step not so easy to control. O. oeni displays many adaptation tools to resist the harsh wine conditions which explain its natural dominance at this stage of winemaking. Previous findings showed that capsular polysaccharides and endogenous produced dextran increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 92 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…The authors suggested that with the wide presence of EPS-biosynthesis genes and because O. oeni is a species with a reduced genome highly specialised towards wine stress, EPS must be relevant to the robustness of O. oeni. This was later confirmed by Dimopoulou et al (2018), who clearly demonstrated a relationship between EPS-production, survival and MLF activity by O. oeni cultures. Furthermore, they showed that low pH ex and ethanol induced EPS genes, cementing the link between the presence of EPS genes in O. oeni and its role in surviving wine stress.…”
Section: Role Of Exopolysaccharidesmentioning
confidence: 67%
See 1 more Smart Citation
“…The authors suggested that with the wide presence of EPS-biosynthesis genes and because O. oeni is a species with a reduced genome highly specialised towards wine stress, EPS must be relevant to the robustness of O. oeni. This was later confirmed by Dimopoulou et al (2018), who clearly demonstrated a relationship between EPS-production, survival and MLF activity by O. oeni cultures. Furthermore, they showed that low pH ex and ethanol induced EPS genes, cementing the link between the presence of EPS genes in O. oeni and its role in surviving wine stress.…”
Section: Role Of Exopolysaccharidesmentioning
confidence: 67%
“…The membrane has undergone a modification of its composition which releases the dimeric Lo18 protein where after the function of Lo18 becomes protecting intracellular proteins as oligomers (Maitre et al 2014). The cell wall has undergone repair and modification, and EPS genes are induced (Constantini et al 2015), leading to production of, for example capsular polysaccharides, building a third protective barrier against acid, ethanol and SO 2 (Dols-Lafargue et al 2008, Dimopoulou et al 2018. Thioredoxin and glutathione pathways continue to be utilised to maintain the thiol redox state.…”
Section: Key Stress Impacts and Responsesmentioning
confidence: 99%
“…Apart from cell integrity of freeze-dried O. oeni, cell surface morphology (Figure 2) was detected using SEM and more extracellular substances between freeze-dried cells were found with acid acclimation. Comparably, Dimopoulou et al (2018) found that the production rate of exopolysaccharides was increased in the presence of single stress factors such as pH and ethanol.…”
Section: Discussionmentioning
confidence: 89%
“…There is evidence that consumption of such products can have health benefits. This in turn has led to research to specifically identify EPS that could be potentially developed as medicines for human and animal use ( Castro-Bravo et al, 2017 ; Dimopoulou et al, 2018 ; Pérez-Ramos et al, 2017a , b , 2018 ). Therefore, in the search for novel bacterial producers of the extracellular 2-substituted-(1,3)-β- D -glucan, we isolated a P. ethanolidurans (CUPV141) strain for the first time from a ropy cider of the Basque Country.…”
Section: Discussionmentioning
confidence: 99%